Is Person-Group Value Congruence Always a Good Thing? Values and Well-Being Among Maladjusted Teens and Their Peers - Bojanowska, Agnieszka; Piotrowski, Konrad (Frontiers in Psychology, 2020)
In the present study, we analysed relationships between values, well-being and person-group value consistency in two samples: teens under court mandated supervision (n=51) and teens from the general population (n=49). Results showed, that supervised teens experienced lower satisfaction with life, placed more value in stimulation, hedonism and power, and less in universalism and benevolence. They also experienced lower satisfaction when they valued stimulation, hedonism and face and higher satisfaction when they valued conformity-rules and universalism-tolerance. These results show, that valuing the things that the group also values at a high level (here: for hedonism and stimulation) may not always be a positive force, especially when the environment is problematic, whereas going against the values of the maladjusted group (here: for universalism) may be beneficial for well-being. However, when we calculated a direct index of person-group congruence it correlated positively with satisfaction among supervised teens for the values of Achievement, Stimulation, Security-Personal and Universalism-concern, while congruence for Power-Dominance correlated with satisfaction negatively among the supervised teens, suggesting a slight but direct limit to the congruence effect.